Development of an integrated discounting strategy based on vendors’ expectations using FAHP and fuzzy goal programming - Ucal Sari, Irem (Technological and Economic Development of Economy, 2018)
The main goal of a company is to increase its market share and total profits at the same time. However, these two objectives conflict if discount rates are applied to vendors. The objective of this paper is to develop an integrated discounting strategy method to effectively manage the transactions of the vendors by determining the optimum discount rates which balance the increase on the market share and the total profit. With the proposed methodology which utilizes fuzzy analytic hierarchy process and fuzzy goal programming, determination of the discount rates of each vendor under different discounting strategies is facilitated. This enables the vendors to choose the most suitable discounting strategy with the best applicable discount rate and enables the managers to predict the transactions of the vendors. The proposed method is validated with a numerical study conducted on a pilot region of an international company. First published online: 07 Mar 2017